PERJUMPAAN DAN DIALOG RITUAL ZAISO SUKU WEWEWA DENGAN IMAN KRISTEN - Martha Ari Molla (Jurnal Pendidikan Kristen dan Ilmu Teologi Marturia, 2022)
AbstractThe presence of a church will only be meaningful if it can theology according to the context. Therefore, dialogue between the Bible and culture is a demand that must be pursued by the church so that the appreciation of the Christian faith can be relevant to the local cultural context in which the church is present and works. It must be admitted that so far the church has tended to be identical with Western culture, which is actually unable to see values in other cultures, so that other cultures outside of Western culture are considered infidels. This has resulted in the proclamation of the Gospel which tends to be identical with Western culture, not easily accepted by other cultures outside of Western culture. The Sumba Christian Church (GKS) is a church resulting from the Dutch zending gospel message and also a Calvinist church, rejecting all forms of prayer and worship to Marapu. Without in-depth study, it is a fact that church members have stronger relations with culture/customs because it is supported by the kabisu/clam system, so that their participation in the zaiso ritual is a form of respect for ritual order and kabisu attachment. AbstrakKehadiran gereja hanya akan bermakna jika dapat berteologi sesuai dengan konteks. Oleh karena itu, dialog antara Injil dan budaya merupakan tuntutan yang harus diupayakan oleh gereja agar penghayatan iman Kristen dapat relevan dengan konteks budaya lokal di mana gereja hadir dan berkarya. Harus diakui bahwa selama ini gereja cenderung identik dengan budaya Barat yang sebenarnya tidak mampu untuk melihat nilai-nilai dalam budaya lain, sehingga budaya lain di luar budaya Barat dianggap kafir. Hal ini mengakibatkan pewartaan Injil yang cenderung identik dengan budaya Barat, tidak mudah diterima oleh budaya-budaya lain di luar budaya Barat. Gereja Kristen Sumba (GKS) adalah gereja hasil pekabaran Injil zending Belanda dan juga gereja aliran Calvinis, menolak semua bentuk doa dan penyembahan kepada Marapu. Tanpa suatu penelitian mendalam bahwa adanya kenyataan anggota jemaat yang memiliki relasi lebih kuat dengan budaya/adat-istiadat karena didukung oleh sistem kabisu/clam, sehingga keikutsertaan mereka dalam ritual zaiso sebagai bentuk menghormati tata tertib ritual dan keterikatan kabisu.